The answer to the question is boneless
Answer 38.6
Step-by-step explanation:
21 x .84 = 17.64
17.64 + 21 = 38.64
There are a few ways to solve this. The method I will use is the substitution method. Since they give us a "y = " statement, we can replace the y in the second equation with what it gives us to the right of the equal sign.
- 3x + 6(- 2x - 1) = 24
Simplify by using the distributive property.
- 3x + 6(- 2x) + 6(- 1) = 24
- 3x - 12x - 6 = 24.
Combine like terms
- 15x - 6 = 24
Add 6 to each side.
- 15x = 30
Divide both sides by - 15 to isolate variable X
x = 30 / - 15
x = - 2.
Now plug in the x-value we've found back into the first equation.
y = - 2( - 2) - 1
y = 4 - 1
y = 3
Your answer is (- 2, 3)
Answer:
C
Step-by-step explanation:
Just re-draw the triangle reflecting the y-axis
Answer:
The one moves up a tenth until it gets to 1.
Step-by-step explanation: